Variaç\~oes na renda real n\~ao captadas pelo PIB: Decomposiç\~ao em efeito termos de troca e efeito preços relativos entre comerciáveis e n\~ao comerciáveis - Brasil (1948-2018) - Estêv\~ao Kopschitz Xavier Bastos; Beatriz Cordeiro Araujo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– The trading gains resulting from changes in terms of trade or relative prices between tradable and non-tradable goods and services are not captured by standard real GDP (RGDP) calculation. The macroeconomic aggregate that does so is the real gross domestic income (RGDI). The System of National Accounts 2008 handbook (SNA, 2008) highly recommend that RGDI be an integral part of the System of National Accounts, but it is not calculated in Brazil. In this text, we extend, improve and update the calculation - previously presented in other works of the authors - of this variable for the Brazilian economy for the 1948-2018 period, including the separation of terms of trade and relative prices effects, present in the international literature, although not in SNA 2008. The difference between RGDP and RGDI is relevant for open economies and in periods of great variations in terms of trade or relative prices, which is the case in some periods for Brazil.
Keywords: E01; 330; terms of trade; trading gains; real gross domestic income; gross domestic product; national accounts